MIGRATING AUTOLUX WEBSITE FROM MODX TO PHALCONPHP WITH FURTHER DEVELOPMENTS (SEARCH ENGINE OPTIMIZATION AND MOBILE APPLICATION SUPPORT IMPLEMENTATION) - Tanjung, Hana; Gestel, Bert van; Andjarwirawan, Justinus (Jurnal Informatika, 2017)
Autolux Project is owned by DTT Multimedia B.V. Autolux is a platform for car lovers sharing their information about favorite or latest cars. The website was built in MODx (CMS framework) which considered being old and heavy by the company. With that very reason, a project to migrate the website from MODx into PhalconPHP (pure PHP framework) was started. Migrating website from MODx to PhalconPHP was a success, and to boost the website popularity, the first thing to do is to implement the SEO standards. Another demand by the company was for the website to be responsive and using OOP standarts. Responsive website can be reached by using the help of libraries. PhalconPHP already implemented OOP, thus the developer will follow the MVC pattern given and refine it by doing more separation of concerns. Later on, the developer also put more refinements on the website to boost the speed of page loading, support multilingual, and management system.